Rosiglitazone and Pioglitazone Alter Aromatase Kinetic Properties in Human Granulosa Cells. (19th December 2011) - Araki, Takako; Varadinova, Miroslava; Goldman, Michael; Rosenwaks, Zev; Poretsky, Leonid; Seto-Young, Donna
Abstract : We have previously reported that, in human granulosa cells, thiazolidinediones rosiglitazone and pioglitazone inhibit estrogen synthesis by interfering with androgen binding to aromatase, without an effect on aromatase mRNA or protein expression. In the current paper, we explore the effects of rosiglitazone and pioglitazone on the aromatase enzyme kinetic properties in human granulosa cells. The cells were incubated with various concentrations of testosterone or androstenedione, with or without rosiglitazone or pioglitazone. Estradiol and estrone concentrations in the conditioned tissue culture medium were measured by radioimmunoassay or immunosorbent assay. When testosterone was used as substrate, rosiglitazone or pioglitazone inhibited theV max by 35% (P < 0.001 ) and 24% (P < 0.001 ), respectively. When androstenedione was used as substrate, both rosiglitazone or pioglitazone inhibitedV max by 13% (P < 0.007 ). We conclude that rosiglitazone or pioglitazone has no effect onK m but inhibitsV max of aromatase in human granulosa cells, therefore, acting as noncompetitive inhibitors.